PENGARUH AKUNTABILITAS, TRANPARANSI DAN KUALITAS SDM TERHADAP PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA - Cantona, Fredrik; Prayogo, Youdhi; Muthmainnah (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of Accountability, Transparency and Quality of Human Resources on APBDes in Villages in Limun District, Sarolangun Regency. This study uses a quantitative approach with primary data in the form of observations, interviews and questionnaires. The population in this study were 11 villages with a sample of 77 people. The sample was taken using a purposive sampling method. In this study using multiple linear regression analysis and testing the hypothesis on the T test and F test and analysis of the coefficient of determination. The results of this study indicate that: Accountability has no significant effect on APBDes Management. Transparency has a significant effect on APBDes Management. And the quality of human resources has a significant effect on APBDes Management. For simultaneous test results (F test), namely Accountability, Transparency and Quality of Human Resources simultaneously influence APBDes Management. The results of the coefficient of determination (R2) show that the independent variables namely Accountability, Transparency and HR Quality explain the dependent variable (APBDes management) of 59.4%. the remaining 40.6% is influenced by other variables not examined in this study.